Effect of Mannose-Binding Lectin (protein A) 1 (MBL1) Gene Polymorphisms on Milk Production Traits and Somatic Cell Count in Holstein Dairy Cattle - Metin Kiyici, J; Daldaban, F; Arslan, K; Akyüz, B; Kaliber, M; Çinar, MU (Journal of the Hellenic Veterinary Medical Society, 2025)
This study was conducted to determine polymorphisms (rs479779108 G>A, rs109492835 G>A, rs453019355 T>C) in mannose-binding lectin-1 (MBL1) gene and to investigate their effects on milk yield (305 d, kg), milk composition (fat %, dry matter %, density %, protein %, freezing %, lactose %) and milk quality traits (somatic cell count, electrical conductivity and pH) in Holstein cows. For this purpose, 166 blood and 1660 milk samples of 166 Holstein cows in their 2nd lactation were used. All possible genotypes for the MBL1 gene (rs479779108 G>A – AvaII) (AA, AG, GG), rs109492835 G>A MaeII (AA, AG) and rs453019355 T>C HaeIII (CC, TC, TT) were observed in the studied population. While the only rs453019355 T>C polymorphisms was found to be associated with EC (P<0.05), all three SNPs (rs479779108 G>A, rs109492835 G>A, rs453019355 T>C) were found to be associated with the SCC trait (P<0.05). In the examined population, rs109492835 was found to be associated with density and protein, while rs453019355 was found to be associated with fat, protein, freezing point, and milk yield characteristics.